Identification of Carbohydrate and Glucose Content in Bread Produced by UMKM XYZ - Lusiana Lusiana; Ilma Munaya; Nur Fitria Andani; Muhammad Azman; Risky Risky (Pakis Journal Institute, 2026)
This study aimed to identify the carbohydrate content and glucose levels in breads produced by the small and medium-sized enterprise (SME) XYZ, which included five variants: cheese bun, chocolate bun, chocolate cheese, pizza, and coffee bun. The carbohydrate content was tested using the Luff-Schoorl method, which is commonly employed for determining moderate carbohydrate levels due to its low error margin of approximately 10%. The results of the carbohydrate tests for the different bread variants from SME XYZ were as follows: for chocolate cheese, the first and second tests yielded 52.739 and 53.389, respectively; for chocolate bun, 43.525 and 47.080; for cheese bun, 31.385 and 33.826; for pizza, 38.073 and 43.418; and for coffee bun, 47.191 and 47.029. Based on these results, it can be concluded that the highest carbohydrate content was found in the chocolate cheese sample from both test sessions, while the lowest content was observed in the cheese bun sample.